2020
DOI: 10.3390/jcm9113618
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal Reflux: A State-of-the-Art Algorithm Management for Primary Care Physicians

Abstract: Laryngopharyngeal reflux (LPR) is a common disease in the general population with acute or chronic symptoms. LPR is often misdiagnosed in primary care because of the lack of typical gastroesophageal reflux disease (GERD) symptoms and findings on endoscopy. Depending on the physician’s specialty and experience, LPR may be over- or under-diagnosed. Management of LPR is potentially entirely feasible in primary care as long as General Practitioners (GPs) are aware of certain “red flags” that will prompt referral t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 81 publications
(126 reference statements)
0
27
0
11
Order By: Relevance
“…In a prospective study in pregnant women ( n = 144) with symptoms of heartburn and/or reflux requiring treatment, Gaviscon Advance was effective in 91% of patients as assessed by the investigator and 90% as assessed by the patients 84 . Alginate compounds have also been recommended for use in extra‐esophageal GERD as an adjunctive therapy, for example, in reflux‐associated laryngopharyngitis 85,86 Statement 18: PPIs are generally safe drugs but should be used with caution when taken on a long‐term basis Grade of recommendation: Strong Evidence level: Moderate Consensus level: 100% (Strongly agree—100%) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study in pregnant women ( n = 144) with symptoms of heartburn and/or reflux requiring treatment, Gaviscon Advance was effective in 91% of patients as assessed by the investigator and 90% as assessed by the patients 84 . Alginate compounds have also been recommended for use in extra‐esophageal GERD as an adjunctive therapy, for example, in reflux‐associated laryngopharyngitis 85,86 Statement 18: PPIs are generally safe drugs but should be used with caution when taken on a long‐term basis Grade of recommendation: Strong Evidence level: Moderate Consensus level: 100% (Strongly agree—100%) …”
Section: Resultsmentioning
confidence: 99%
“…Following the algorithm, PPIs are recommended for the treatment of patients with persistent symptoms of GERD 79 . Additionally, alginates can be prescribed as an adjunctive therapy to PPIs in various circumstances such as during pregnancy 84 or even in extra‐esophageal GERD such as laryngopharyngitis or when patients are only partially responsive to PPIs 85,86 . Although alginates are a very safe compound for clinical use, there has to be some caution in use in patients with heart failure and chronic kidney diseases as they contain sodium or potassium.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the precise prevalence of LPR, the consensus of LPR diagnoses needs to be reached and a golden standard approach needs to be established to confirm LPR [ 24 ]. Further studies on the prevalence of LPR need to combine the subjective symptom assessment instruments with objective diagnostic tools, such as 24-h multichannel intraluminal impedance-pH metry (MII-pH metry), GI endoscopy, and methods for detection of pepsin in saliva [ 1 , 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the prevalence of LPR was 8.1% of Chinese college students [ 7 ]. Evidence shows that the LPR can be alleviated by lifestyle intervention [ 8 ], thus it is important to detect the risk factors to prevent LPR.…”
Section: Introductionmentioning
confidence: 99%
“…), with approximately only 10% of patients needing surgical intervention. 4,6,7 In this editorial, we present our management pathway for patients presenting with GERD/LPR from the perspective of a thoracic surgeon.…”
Section: Introductionmentioning
confidence: 99%